160k views
1 vote
Help meh please because I don’t understand this

Help meh please because I don’t understand this-example-1
User Kortemy
by
4.9k points

1 Answer

2 votes

Answer:


\textsf{a) \quad $(2)/(5)$}


\textsf{b) \quad $(5)/(2)$}

Explanation:

Question a)

Given expression:


\left((4)/(25)\right)^{(1)/(2)}

Rewrite 4 as 2² and 25 as 5²:


\implies \left((2^2)/(5^2)\right)^{(1)/(2)}


\textsf{Apply the exponent rule} \quad \left((a)/(b)\right)^c=(a^c)/(b^c):


\implies \frac{(2^2)^{(1)/(2)}}{(5^2)^{(1)/(2)}}


\textsf{Apply the exponent rule} \quad (a^b)^c=a^(bc):


\implies \frac{2^{(2\cdot(1)/(2))}}{5^{(2\cdot(1)/(2))}}


\implies (2^1)/(5^1)


\implies (2)/(5)

Question b)

Given expression:


\left((4)/(25)\right)^{-(1)/(2)}

Rewrite 4 as 2² and 25 as 5²:


\implies \left((2^2)/(5^2)\right)^{-(1)/(2)}


\textsf{Apply the exponent rule} \quad \left((a)/(b)\right)^c=(a^c)/(b^c):


\implies \frac{(2^2)^{-(1)/(2)}}{(5^2)^{-(1)/(2)}}


\textsf{Apply the exponent rule} \quad (a^b)^c=a^(bc):


\implies \frac{2^{(2\cdot -(1)/(2))}}{5^{(2\cdot -(1)/(2))}}


\implies (2^(-1))/(5^(-1))


\textsf{Apply the exponent rule} \quad a^(-n)=(1)/(a^n):


\implies (1)/(2^1 \cdot 5^(-1))


\implies (1)/(2 \cdot 5^(-1))


\textsf{Apply the exponent rule} \quad (1)/(a^(-n))=a^n:


\implies (5^1)/(2)


\implies (5)/(2)

User Pamma
by
5.4k points